CONTRACEPTIVE USE AMONG WOMEN WITH CHRONIC NON-COMMUNICABLE DISEASE IN ADDIS ABABA PUBLIC HOSPITALS, ETHIOPIA - Gebrekidan, Hailay; Gebretinsae, Teame; Alemayehu, Mussie; Mirutse, Gebrameskel (Ethiopian Journal of Reproductive Health, 2020)
Women with chronic non-communicable diseases are at higher risk of adverse pregnancy outcomes, which may be minimized through optimal preconception care and appropriate contraceptive use. Information on the contraceptive use and affecting factors among women with chronic non-communicable diseases in Ethiopia is rare. The objective of this study was to assess the magnitude of contraceptive use and associated factors among women with chronic non-communicable diseases in Addis Ababa’s, public hospitals. A hospital based cross-sectional study was performed on 357 women with chronic non-communicable diseases. Systematic sampling method was used to select the study participants. The Data were collected using interviewer administered structured questionnaires and was analysed using SPSS version 20.0. Bivariate and multivariate logistic regression at 95% CI and P < 0.05 was used to determine the final predictor in the model. Of the total women, only 124(34.2%) were contraceptive users. Majority of women with chronic non-communicable diseases were diabetic 140(39.2%), and hypertensive 134(37.5%). Those who discussed with their husband and got counselling were higher contraceptive users with AOR=2.5, 95% CI :( 1.3, 5.1) and AOR= 3.6, 95% CI (1.6, 8) respectively. Discussion with husband and counselling about contraceptive use were found the main predictors of contraceptive use.